A Conceptual Approach to Teaching Mathematics to Students With Intellectual Disability. Issue 2 (3rd March 2016) - Göransson, Kerstin; Hellblom-Thibblin, Tina; Axdorph, Eva
Abstract : Swedish compulsory school for students with intellectual disability (ID) has been criticized for focusing on care and not presenting the students with enough knowledge-related challenges. The purpose of this study is to investigate how a conceptually-based mathematics curriculum can be interpreted and constructed for students with ID. A total of 18 mathematics lessons in 6 classes for students with ID were filmed, and the teachers were interviewed in connection with the lessons. A qualitative content analysis approach was used to identify aspects of mathematical competency content and to analyze the teaching. Three major groups of teaching strategies are identified: pedagogical mathematics activities, focusing on students' perceptions of mathematical content, and encouraging dialogue between students.